Planning Optimum Logging Operations through Precision Forestry Approaches - Gülci, Neşe; Akay, Abdullah Emin; Erdaş, Orhan; Wing, Michael G.; Sessions, John (EJFE, 2015)
In this study, it was aimed to determine optimum logging operations by using Geographical Information System (GIS) techniques as one of the effective tools of a precision forestry approach. In the first stage of the application process, a high resolution Digital Elevation Model (DEM) of the study area was produced by using Real Time Kinematic GPS in the field. Then, the DEM was used to classify the area into slope classes specified by the International Union of Forest Research Organizations (IUFRO). A map for the optimum logging operations was generated for two scenarios (i.e. maximum productivity and minimum residual stand damage) considering current terrain conditions. Four different logging methods were evaluated: ground skidding logs using a portable winch integrated with skidding cone, winching logs by using a farm tractor, downhill sliding of logs by chute system with gravity, and controlled sliding of logs downhill by chute system integrated with portable winch. During the assessment of logging methods, the results from the previous empirical studies conducted in similar stand characteristics and topographical conditions were used. For both scenarios, results indicated that skidding by portable winch integrated with skidding cone was the optimum logging method for more than half of the study area, followed by downhill sliding by chute system and controlled sliding by chute system integrated with portable winch.
Keywords: Logging operations; Precision forestry; GIS; RTK-GPS